Bacteriophage therapy against plant, animal and human pathogens - Doffkay, Zsolt; Dömötör, Dóra; Kovács, Tamás; Rákhely, Gábor (Acta Biologica Szegediensis, 2015)
Bacteriophages are specific infective agents of various bacteria. They can be divided into various groups according to their life cycle. The lytic phages kill their host cells and this property can be applied for selective elimination of pathogenic bacteria. The first bacteriophage treatment was described one hundred years ago, and phage therapy had been extensively used till the Second World War. Upon appearance of antibiotics, the medical application of phages retrograded in most parts of the world. In the last decades, owing to the costs of development of new antibiotics and rapid emergence of multidrug-resistant bacteria, this old approach was revitalized and phage-based treatment was legalized from the middle of the last decade. Here, we summarize the current knowledge on phage therapy, its advantages and potential drawbacks. The application of phages against plant pathogens, especially Erwinia amylovora is discussed. Moreover, the current status of phage therapy against food-borne, animal and human pathogens is also presented. Among these, special focus is set on phages of Staphylococcus aureus, Salmonella typhimurium and Listeria monocytogenes. Phage cocktails against L. monocytogenes and E. amylovora have been already commercialized.